Site Suitability Analysis For Municipal Solid Waste Disposal In Jigjiga City, Somali Region, Ethiopia - Eyob Derese (ASTU, 2022)
Solid Waste Management Has Become A Challenge Problem In The Modern World As A Result Of Increased Different Activities And Rapid Urbanization; In The Past Fifteen Years The Number Of Population And Rate Of Urbanization In Jigjiga City Was Slow, In This Case The City Administration Select A Place As Solid Waste Disposal Site Out Skirt Of The City Without Scientific Investigation And Creating The Criteria, But Now A Days Jigjiga Become Somali Regional State Capital City And The Main Trade Market Place In East Part Of Ethiopia So That The Rate Of Urbanization And Population Growth Become Increased In This Case The Solid Waste Generation Amount Become High, In Addition The Nature Of Urbanization Trained Of Jigjiga City Is Horizontal So Disposal Site??S Move To Center Of The City In This Case The Disposal Site Become Main Source Of Social Health And Environment Pollution Problems, The Aim Of The Study To Analyze And Identify Suitable Site For Municipal Solid Waste Disposal For Jigjiga City, In This Study, The Main Method Used Geographic Information System ??Based Multi-Criteria Analysis Has Been Adopted To Select Suitable Sites For Solid Waste Disposal; The Main Data In This Study Includes Ground Survey Data, Digital Elevation Model. Landsat8. As Well As Questioners, Interviews And Observation; Analytical Hierarchy Process Pair-Wise Comparison Matrix Was Used To Derive Weight For The Factors Parameters; Based On The Consistence Ratio Obtained 0.083987 > 0.1 So This Is Acceptable; On The Dwellers Respond Obtained 48.3 % Of The Respondent Use Open Dump Site, 15.5% Are Use Valley , Based On The Information Got From The Respondents Unprotected And Mismanagement Of Solid Disposal System This Caused Different Social Health And Environmental Problem, For Example The Respondent Inform Typhoid, Diarrhea, Cough, Malaria Are The Main Health Problem Rise From Disposal Area, This Shows That The Disposal Areas Are Open Dump Site And Also Dwellers Also Used Self-Disposal System, As The Result Of The Final Suitability Map Showed That 26.87 % Of The Entire Study Area Is Categorized As Highly Suitable Site, The Suggested Areas As Highly Suitable For Solid Waste Dumping Site Fall In Kebele 22, Kebele 12, Kebele 18 And Kebele 16 The North, North West, South East And South West Direction From The City, Finally This Is Recommended To The City Administration The Rates And Volumes Of Solid Waste Generated From The Municipality Should Be Carefully Determined To Further Decide The Dimension Of The Landfill Site During Construction.
Keywords: Analytical Hierarchy process, Geographic information system, Jigjiga City, Multi criteria Analysis